2019
DOI: 10.1002/anie.201903957
|View full text |Cite
|
Sign up to set email alerts
|

Gold Difluorocarbenoid Complexes: Spectroscopic and Chemical Profiling

Abstract: Gold carbenes of the general type [LAu = CR 2 ] + are sufficiently long-lived for spectroscopic inspection only if the substituents compensate for the largely missing stabilization of the carbene center by the [LAu] + fragment. p-Donation by two fluorine substituents (R = F) is insufficient;r ather,d ifluorocarbene complexes are so deprived in electron density that they sequester even "weakly coordinating" anions such as triflate or triflimide.T his particular bonding situation translates into unmistakable car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 96 publications
3
18
1
Order By: Relevance
“…Crystallographic parameters and refinement details for all complexes are listed in Table S1 . Overall, metrical parameters for triarylazoimidazoles in 5, 7 – 10 are similar to those reported for structurally relevant azocompounds [ 17 , 18 , 19 , 23 , 35 , 36 ] and imidazole derivatives [ 37 , 38 ]. CCDC 2058877-2058881 contain the supplementary crystallographic data for this paper.…”
Section: Methodssupporting
confidence: 76%
“…Crystallographic parameters and refinement details for all complexes are listed in Table S1 . Overall, metrical parameters for triarylazoimidazoles in 5, 7 – 10 are similar to those reported for structurally relevant azocompounds [ 17 , 18 , 19 , 23 , 35 , 36 ] and imidazole derivatives [ 37 , 38 ]. CCDC 2058877-2058881 contain the supplementary crystallographic data for this paper.…”
Section: Methodssupporting
confidence: 76%
“…Several synthetic strategies have been established for their preparation (see Scheme 1). They include the oxidative addition of CF 3 I to organo gold(I) complexes, [10, 22, 24, 28–31] and transmetallation reactions of halido organo gold compounds with Cd(CF 3 ) 2 ⋅DME (DME=1,2‐dimethoxyethane) [22, 31, 32] or of halido or alkoxido organo gold complexes with the Ruppert–Prakash reagent trimethyl(trifluoromethyl)silane (TMSCF 3 ) in the presence of a nucleophilic fluoride source when required [23, 26, 33–36] . Reactions of [Au(CN) 4 ] − with ClF in CH 2 Cl 2 [37] and [Au(CN) 2 ] − with [ClF 4 ] − in CHFCl 2 [38] were not selective and yielded several products that could not be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in trifluoromethyl gold complexes led to studies on their usage in gold‐mediated C−E (E=C, N, Hal.) bond formations and on further functionalizations of these complexes over the last decade [9, 10, 12, 24–27, 29, 33–36, 41, 42] . Despite the variety of known trifluoromethyl gold complexes, only four complexes containing trifluoromethyl and fluorido ligands at the same gold center have been isolated, namely [Au(CF 3 )(4‐CH 3 −C 6 H 4 )F(PPh 3 )], [9] [Au(CF 3 )(4‐F−C 6 H 4 )F(PCy 3 )], [9] [PPh 4 ]‐[Au(CF 3 ) 3 F] [10] and [PPh 4 ][ trans ‐Au(CF 3 ) 2 F 2 ] [12] (see Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Fürstner et al [ 67 ] showed that (trifluoromethyl)gold(I)triphenylphosphine in dichloromethane can be used for the production of difluorocyclopropanes at low temperatures. The advantage of the method is its stereoselectivity.…”
Section: Reviewmentioning
confidence: 99%